An Unusual Cause of Knee Pain: Periosteal Glomus Tumor of the Distal Femur - Hyung Joon Cho; Kyung-Sik Ahn; Chang Ho Kang; Yura Kim; Jong Hoon Park (대한영상의학회지, 2018)
Glomus tumors are rare neoplasms that characteristically occur in subungual regions, but may also be found in other regions of the body. The clinical diagnosis of this tumor may be difficult if the tumor is located in an extradigital site. Most extradigital glomus tumors form in superficial locations. Herein, we present the case of a 34-year-old woman who experienced chronic knee pain with pinpoint tenderness resulting from a deep-seated periosteal glomus tumor of the distal femur. Extradigital glomus tumors should be considered in the differential diagnosis when characteristic clinical features and imaging findings indicative of glomus tumors are present, even if the tumor is located within deep tissues.